BLOCKADE OF ENDOTHELIAL GROWTH FACTOR, ANGIOPOIETIN-2, REDUCES INDICES OF ARDS AND MORTALITY IN MICE RESULTING FROM THE DUAL-INSULTS OF HEMORRHAGIC SHOCK AND SEPSIS. Issue 2 (February 2016) - Lomas-Neira, Joanne L.; Heffernan, Daithi S.; Ayala, Alfred; Monaghan, Sean F.
Abstract : ABSTRACT: We have demonstrated hemorrhagic shock "priming" for the development of indirect acute respiratory distress syndrome (iARDS) in mice following subsequent septic challenge, and show pathology characteristic of patients with iARDS, including increased lung microvascular permeability and arterial PO2 /FI02 reduced to levels comparable to mild/moderate ARDS during the 48 h following hemorrhage. Loss of endothelial cell (EC) barrier function is a major component in the development of iARDS. EC growth factors, Angiopoietin (Ang)-1 and 2, maintain vascular homeostasis via tightly regulated competitive interaction with tyrosine kinase receptor, Tie2, expressed on ECs. Ang-2/Tie2 binding, in contrast to Ang-1, is believed to produce vessel destabilization, pulmonary leakage, and inflammation. Recent clinical findings from our trauma/surgical intensive care units and others have reported elevated Ang-2 in the plasma from patients that develop ARDS. We have previously described similarly elevated Ang-2 in plasma and lung tissue in our shock/sepsis model for the development of iARDS, and demonstrated effective reduction in indices of inflammation and lung tissue injury following siRNA inhibition of Ang-2 protein synthesis. In this study we show that Ang-2 in lung tissue and plasma spikes following hemorrhage (priming) and remain elevated at sepsis induction. In addition, that transient inhibition of Ang-2 function immediately following hemorrhage, suppressing priming, but not following sepsis, impacts the development of iARDS in our model. Our data demonstrate that selective temporal blockade of Ang-2 function following hemorrhagic shock priming significantly improved PO2 /FIO2, decreased lung protein leak and indices of inflammation, and improved 10-day survival in our murine model for the development iARDS.